OPTIMALISASI MANAJEMEN TENAGA PENDIDIK, KEPENDIDIKAN, DAN PESERTA DIDIK UNTUK MEWUJUDKAN LAYANAN PENDIDIKAN YANG BERKUALITAS - WINTA GADIS OKTAPIANA; NUR WAFIAH; YUDRIZKA UJLIFAT; AZIZAH NURUL HUSNA R; SULKIFLI SULKIFLI (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2026)
Quality educational services are a primary pillar in creating superior and competitive human resources in the global era. However, many educational institutions still face various challenges in managing the education system comprehensively, especially in the aspects of educational management, educators and educational staff, and students. This research was conducted to describe efforts to optimize these three components to support the improvement of educational service quality. The approach used is descriptive qualitative through a literature study of various academic sources and educational policies. The results of the study indicate that well-planned educational management, training and competency development for educators and educational staff, and continuous student development significantly contribute to the quality of educational services. Therefore, synergy and integrated management are needed so that the educational process can run effectively and be oriented towards quality improvement.